Bilateral spontaneous simultaneous femoral neck occult fracture in a middle-aged man due to osteoporosis and vitamin D deficiency osteomalacia: A case report and literature review. (2019) - Fukui, Kiyokazu; Kaneuji, Ayumi; Hirata, Hiroaki; Tsujioka, Jun-ichi; Shioya, Akihiro; Yamada, Sohsuke; Kawahara, Norio
Highlights: Physicians should take spontaneous femoral neck occult fracture into consideration if they report groin pain or difficulty in walking, even when findings from plain X-ray are normal. In a patient with spontaneous femoral neck occult fracture, diagnosing and treating the underlying etiology of osteoporosis and osteomalacia are essential for improving prognosis. This is the first report of a case of bilateral spontaneous simultaneous occult fracture of the femoral neck caused by osteoporosis and osteomalacia in a middle aged man. Abstract: Introduction: Bilateral stress fracture of the femoral neck is very rarely seen in healthy young patients who are neither athletes nor military recruits. Presentation of case: The present report describes a 51-year-old male patient, not an athlete and with no previous history of disease, who developed bilateral stress fracture of the femoral neck without displacement. Discussion: Simultaneous bilateral femoral neck fracture is a rare injury. In the present case, two factors predisposed to bilateral occult fracture of the femoral neck. The first was osteoporosis due to the patient's smoking and alcohol abuse. The second was vitamin D deficiency osteomalacia associated with inadequate sun exposure. Conclusion: All patients who present with spontaneous hip pain should be evaluated for osteoporosis and osteomalacia and assessed for underlying occult fracture if they report groin pain or difficulty in walking, even when findings from plain X-ray are normal, to improve prognosis in this rare and serious condition.